2021
DOI: 10.4102/hts.v77i4.6747
|View full text |Cite
|
Sign up to set email alerts
|

The science of congregation studies and psychographic segmentation: O come all ye thinking types?

Abstract: Previous research employing Jungian psychological type theory has both demonstrated that Church of England inherited congregations have problems engaging thinking types and suggested that fresh expressions of church have failed to address that problem. Three previous studies, however, have reported higher proportions of thinking types attending cathedral carol services. The present study was designed to check that finding on a larger sample. The Francis Psychological Type Scales were completed by 941 participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…All three replication studies confirmed Walker's initial findings that cathedral carol services were providing events reaching people whom Sunday activities were finding it hard to reach. 17 In terms of place, two initial studies applying psychological type theory to cathedral visitors reported on 381 visitors to St Davids Cathedral and on 157 visitors to Chester Cathedral. These two initial studies were followed by more substantial studies of 2,327 visitors to St Davids Cathedral 18 and 1,082 visitors to a further four cathedrals.…”
Section: Anglican Cathedralsmentioning
confidence: 99%
“…All three replication studies confirmed Walker's initial findings that cathedral carol services were providing events reaching people whom Sunday activities were finding it hard to reach. 17 In terms of place, two initial studies applying psychological type theory to cathedral visitors reported on 381 visitors to St Davids Cathedral and on 157 visitors to Chester Cathedral. These two initial studies were followed by more substantial studies of 2,327 visitors to St Davids Cathedral 18 and 1,082 visitors to a further four cathedrals.…”
Section: Anglican Cathedralsmentioning
confidence: 99%
“…In the fourth paper, Walker (2015) identified clear demographic differences among those attending cathedral carol services and ordinary Sunday congregations, including a higher proportion of men and a higher proportion of younger people. The research tradition established by Walker in Worcester cathedral and in Lichfield Cathedral has been extended to Bangor Cathedral by Francis, Edwards and ap Siôn (2021) and to Liverpool Cathedral by , Francis, Jones & McKenna (2020, 2021a, 2021b, and Pike (2022).…”
mentioning
confidence: 99%